Preparation method and application of a temperature-sensitive nano-lubricated water-based epoxy synergistic consolidation plugging system

CN122941380APending Publication Date: 2026-10-20CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611281751.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

随着油气勘探持续向鄂北刘家沟组、川渝页岩、陇东致密油等裂缝发育、软硬互层、构造破碎复杂地层推进,原生粒间孔隙、构造节理、次生连通裂隙密集分布,钻井液正压差极易诱发大规模恶性漏失,处理不当会诱发井壁坍塌、钻杆卡钻、井喷等重大安全事故,同时造成大量钻井液损耗、储层侵入污染,严重降低单井经济效益,行业对高效、稳定、适配宽温域的堵漏技术需求迫切

Benefits of technology

本发明通过石蜡温敏微胶囊全包覆胺类固化剂的技术手段,地面及井筒输送阶段固化剂完全与环氧基体隔绝,体系长期保持低黏可泵状态,进入漏失地层达到触发温度后才均匀释放固化剂触发交联反应,有效解决了现有技术中固化时间调控难度大、易在井筒内提前凝胶堵管、无法深入裂缝深部实现封堵的缺陷,提升了施工安全性与封堵有效性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of oil and gas drilling and plugging technology, and discloses a method for preparing and applying a temperature-sensitive, nano-toughened, water-based epoxy synergistic consolidation plugging system. It comprises two parts: paraffin temperature-sensitive microcapsules and a nano-composite epoxy liquid. The paraffin temperature-sensitive microcapsules use fully refined paraffin as the wall material and are coated with an amine curing agent, rapidly releasing the core material upon reaching the phase transition temperature. The nano-composite epoxy liquid is made from a mixture of bisphenol A type epoxy resin, emulsifier, deionized water, polyethylene glycol, xanthan gum, amino-modified nano-silica, and alkali-hydrolyzed lignin, and contains no free curing agent. Before plugging operations, the microcapsules are mixed with the base liquid and pumped into the formation. The formation temperature triggers the release of the curing agent, completing the cross-linking and plugging process. This system can precisely control the curing triggering timing, and the pumping window covers different construction needs. It significantly improves the plugging pressure resistance and temperature aging resistance, effectively solving the defects of existing plugging systems, such as easy pipe blockage, easy re-leakage, and narrow temperature range adaptability. It is suitable for the plugging operations of various oil, gas, and water wells, and has significant industry promotion value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oil and gas drilling and plugging technology, and in particular to a method for preparing and applying a temperature-sensitive nano-toughened waterborne epoxy synergistic consolidation plugging system. Background Technology

[0002] The global incidence of lost circulation (WS) accidents in oil and gas drilling operations has remained around 20% for many years. According to publicly available statistics from the U.S. Department of Energy, the direct cost of remediation due to WS exceeds $4 billion annually worldwide. Domestic data from CNPC and Sinopec field operations show that WS accounts for 72% to 75% of the lost drilling time due to complex accidents, far exceeding other complex downhole conditions such as stuck pipe and blowouts, making it the leading cause of drilling time loss. As oil and gas exploration continues to advance into complex formations with fractures, interbedded soft and hard layers, and fractured structures, such as the Liujiagou Formation in northern Hubei, the Sichuan-Chongqing shale, and the Gansu tight oil field, the dense distribution of primary intergranular pores, structural joints, and secondary interconnected fractures makes it highly susceptible to large-scale malignant WS induction due to positive pressure differentials in drilling fluid. Improper handling can lead to major safety accidents such as wellbore collapse, stuck drill pipe, and blowouts, while also causing significant drilling fluid loss, reservoir invasion and contamination, and severely reducing the economic benefits of single wells. Therefore, the industry urgently needs efficient, stable, and wide-temperature-range plugging technologies.

[0003] Currently, the mainstream technologies in wellbore plugging fallout control ...

[0004] The second type is cement slurry solidification and plugging technology, such as Mobil's published patent US3876006 "Method of alleviating lost circulation". It relies on the cement hydration reaction to generate a high-strength solidified structure, which is suitable for severe leakage conditions in large cracks. However, the hydration reaction is uncontrollable and tends to thicken prematurely in the shallow layers of the formation, making it impossible to transport to the deep parts of the crack. After plugging, drilling is required, which greatly increases non-drilling time.

[0005] The third category is polymer gel plugging technology, such as the composite fiber gel plugging system disclosed in Chinese patent CN107674662A. It relies on polymer cross-linking to form a three-dimensional network to achieve plugging. It can penetrate deeply, but the gelation window is narrow and the temperature and salt resistance is weak. It is prone to drilling blockage and pipe filling safety accidents downhole. After long-term high-temperature aging, the mechanical properties degrade significantly.

[0006] The fourth category is epoxy resin chemical consolidation plugging technology, which is currently a key research direction. For example, Halliburton's published patent US20130008654A1 and Saudi Aramco's authorized patent US11370956B2 both disclose epoxy-based plugging systems. These systems rely on low-viscosity resin entering the fracture and then being thermally triggered to form an integral consolidation structure. They have high bonding strength and low shrinkage. However, most existing systems are solvent-based, which have poor compatibility with water-based drilling fluids widely used in the field. They also have a narrow curing temperature control range and cannot cover formations with a wide temperature range of 50-80℃. Furthermore, they do not incorporate nano-toughening or temperature-sensitive slow-release structures, resulting in insufficient toughness of the crosslinked network and significant mechanical degradation due to high-temperature aging. In addition, the pressure limit for sealing large fractures with a single resin phase is low, and it is impossible to form a synergistic plugging structure with bridging particles, making it difficult to meet the long-term plugging requirements of complex fracture formations. Summary of the Invention

[0007] To address the shortcomings of existing oil and gas drilling plugging technologies, such as narrow temperature range adaptability, premature gel plugging, and low pressure resistance of the plugging layer leading to easy re-leakage, this invention provides a method for preparing and applying a temperature-sensitive nano-toughened waterborne epoxy synergistic consolidation plugging system.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A temperature-sensitive, nano-toughened, waterborne epoxy synergistic consolidation and plugging system is disclosed for plugging operations in fractured, broken, or highly permeable formations during oil and gas drilling. It comprises the following components by weight percentage: 40%–60% bisphenol A type epoxy resin, 5%–12% OP-10 emulsifier, 15%–25% deionized water, 2%–5% polyethylene glycol PEG-3000, 0.2%–1.0% xanthan gum XC, 0.5%–2.0% amino-modified nano-silica, 0.5%–2.0% alkali-hydrolyzed lignin powder, and paraffin temperature-sensitive microcapsules. The paraffin temperature-sensitive microcapsules are made with 48# fully refined paraffin wax as the shell material and 3… The system contains core-shell microcapsules with 3-diethylaminopropylamine as the core material, and the phase transition trigger temperature is 48℃~50℃. The system does not contain free amine curing agents, and all 3-diethylaminopropylamine exists in the form of paraffin thermosensitive microcapsules as the core material. The amount of paraffin thermosensitive microcapsules added is based on the mass of 3-diethylaminopropylamine contained in them accounting for 7% to 11% of the total mass of the system.

[0009] Furthermore, the raw materials for preparing the paraffin thermosensitive microcapsules include, by weight, 100 parts of core material 3-diethylaminopropylamine, 70-85 parts of wall material 48# fully refined paraffin, 8-12 parts of amphiphilic modifier PEG-400, 2-4 parts of low-temperature compatibilizer lauryl alcohol, and 180-220 parts of dispersion medium 60℃ deionized water; the mass fraction of 3-diethylaminopropylamine in the paraffin thermosensitive microcapsules is 49%-56%, and the amount of microcapsules added is calculated according to this ratio to ensure that the total mass of amine curing agent in the system reaches the design value.

[0010] Furthermore, the paraffin thermosensitive microcapsules have a particle size of 10-40 mesh, a core material coverage rate of not less than 92%, and no amine substances leak when the ambient temperature is below 45℃; the leak-sealing system, when left to stand for 48 hours at an environment of 20℃-40℃, has a viscosity change rate of no more than 10% and no premature gelation phenomenon.

[0011] Furthermore, the system is suitable for lost formations with temperatures ranging from 50°C to 80°C; in the system applicable to shallow low-temperature formations with temperatures ranging from 50°C to 60°C, the mass of 3-diethylaminopropylamine in the paraffin thermosensitive microcapsules accounts for 8.5% to 10.5% of the total mass of the system; in the system applicable to high-temperature formations with temperatures ranging from 70°C to 80°C, 0.3% to 0.5% of 2,3-dihydroxynaphthalene retarder is also added to the system.

[0012] Furthermore, paraffin thermosensitive microcapsules and nanocomposite epoxy liquid are prepared independently, wherein the nanocomposite epoxy liquid does not contain free amine curing agents; before on-site leak sealing construction, the paraffin thermosensitive microcapsules are mixed into the nanocomposite epoxy liquid and stirred at a speed of 200r / min to 400r / min for 3min to 8min until the particles are uniformly suspended.

[0013] Furthermore, the preparation of the paraffin thermosensitive microcapsules includes the following steps: A1. Low-temperature melt modified paraffin: The reaction vessel is kept at a constant temperature of 60℃, and 48# fully refined paraffin, PEG-400 and lauryl alcohol are added. The mixture is stirred at 350r / min for 30min to obtain a uniform melted wax phase. A2. Core material dispersion and emulsification: Maintain the reactor temperature at 60℃, add liquid 3-diethylaminopropylamine, and shear at a high speed of 3000r / min for 12min to disperse the amine liquid into tiny droplets of 5μm~18μm, forming an oil-coated amine primary dispersion; A3. Low-temperature quenching and forming: The mixed oil phase is dripped into cold water at 15℃ at a rate of 8mL / min and stirred at a low speed of 250r / min. The low-temperature paraffin quickly solidifies and encapsulates the amine droplets to form a complete core-shell structure. A4. Low-temperature drying: Dry in a 40℃ environment with forced air for 4 hours, and keep the temperature below 45℃ throughout the process to avoid softening and damage of the wax shell. A5. Screening and grading: Screening to obtain complete microcapsule particles of 10 to 40 mesh for later use.

[0014] Furthermore, the preparation of the nanocomposite epoxy liquid includes the following steps: B1. Resin emulsification: Take a measured amount of bisphenol A epoxy resin and preheat it in a 45°C water bath. Add OP-10 emulsifier and stir to mix. Add deionized water dropwise at a uniform rate over 10 minutes through a constant pressure funnel and continue stirring for 10 minutes to form a preliminary oil-in-water emulsion. B2. Introduction of dispersion stabilization system: The metered polyethylene glycol PEG-3000 is pre-dissolved in warm water, poured into the emulsion and stirred for 15 min. The steric hindrance of PEG prevents the resin droplets from agglomerating and separating. B3. Stepwise doping of bifunctional fillers: First, add alkali-hydrolyzed lignin powder under low-speed stirring conditions and stir for 8 minutes. Then, slowly add amino-modified nano-silica that has been ultrasonically dispersed for 10 minutes to eliminate agglomeration into the emulsion and stir for 12 minutes. B4. Thickening and suspension control: Slowly add xanthan gum XC dry powder and stir continuously for 15 minutes to obtain a stable milky white nano-composite epoxy liquid.

[0015] Furthermore, for plugging operations in oil and gas drilling formations with lost circulation at temperatures of 50℃ to 80℃, it can be used alone or in combination with bridging plugging slurry.

[0016] Furthermore, for wide cracks or karst cave-type severe leakage conditions with an opening of more than 1 mm, the aforementioned sealing system and bridging sealing slurry are mixed and used at a volume ratio of 4:1. The bridging sealing slurry, by mass percentage, consists of 2% 7-10 mesh walnut shells, 5% 10-20 mesh quartz sand, 3% 20-40 mesh limestone, 0.3% plant fiber, 0.2% xanthan gum XC, and the balance being water.

[0017] Furthermore, the on-site construction includes the following steps: C1. Prepare a nanocomposite epoxy liquid without paraffin-free thermosensitive microcapsules and store it in a sealed container at room temperature; C2. Before the leak sealing operation, add a measured amount of paraffin thermosensitive microcapsules to the nanocomposite epoxy liquid, and stir at a speed of 200r / min to 400r / min for 3min to 8min until the particles are uniformly suspended to prepare the leak sealing working solution. C3. The plugging fluid is directly pumped into the wellbore. After the working fluid enters the lost formation, the paraffin thermosensitive microcapsules melt and release the curing agent, triggering the epoxy cross-linking reaction to form a solidified sealing layer.

[0018] The present invention has the following beneficial effects: This invention utilizes a technique of fully encapsulating amine curing agents in paraffin thermosensitive microcapsules. During the surface and wellbore transport stages, the curing agent is completely isolated from the epoxy matrix, and the system maintains a low-viscosity, pumpable state for an extended period. Only after entering the lost formation and reaching the trigger temperature is the curing agent uniformly released to trigger the cross-linking reaction. This effectively solves the shortcomings of existing technologies, such as difficulty in controlling curing time, premature gelation and blockage within the wellbore, and inability to penetrate deep into fractures for sealing. This improves construction safety and sealing effectiveness.

[0019] This invention utilizes a synergistic modification technique involving amino-modified nano-silica and alkali-hydrolyzed lignin as bifunctional fillers. The amino-modified nano-silica can participate in the secondary crosslinking reaction of epoxy resin, refine the pores of the crosslinking network, passivate the tips of stressed cracks, and improve the toughness and high-temperature anti-aging properties of the solidified body. The alkali-hydrolyzed lignin can simultaneously enhance the internal bonding force of the solidified body and the interfacial bonding force between the solidified body and the cracked rock wall. This effectively solves the defects of existing technologies, such as the easy slippage and instability of particle bridging, the high brittleness and easy cracking of cement stone, and the significant decline in mechanical properties of conventional epoxy systems after high-temperature aging. The long-term stability of the sealing layer is significantly improved.

[0020] This invention utilizes a fully water-based emulsion system combined with a gradient temperature adaptation scheme, achieving good compatibility with widely used water-based drilling fluids in the field. The amount of curing agent and the ratio of retarder can be adjusted according to the temperature of the lost formation. It can also be used in combination with conventional bridging and plugging slurries to form a composite plugging structure that combines physical bridging and chemical consolidation. This effectively solves the defects of existing technologies, such as incompatibility between solvent-based epoxy and the field system, narrow temperature adaptation range, and insufficient pressure resistance for plugging leaks in wide fractures.

[0021] This system requires no special construction equipment. After the slurry is prepared, it can be directly pumped for operation. After sealing, there is no hard cement plug and no need for subsequent drilling and plugging treatment. It can be widely used for plugging operations of various fractured, broken zones and high-permeability oil and gas reservoirs in the corresponding temperature range. It can also be extended to other underground engineering leakage control scenarios such as coalbed methane and geothermal wells, and has high industry promotion value. Attached Figure Description

[0022] Figure 1 This is a flowchart of a method for preparing a thermosensitive nano-toughened waterborne epoxy synergistic consolidation and plugging system proposed in this invention; Figure 2 The microcapsule encapsulation process proposed in this invention; Figure 3 This is a schematic diagram of the paraffin shell encapsulation and unwrapping proposed in this invention; Figure 4 This is a bar chart comparing the encapsulation rates of different microcapsule samples proposed in this invention with the amine leakage rates at 40℃ for 72 hours. Figure 5 This is a comparison diagram of the pumping windows of different plugging systems proposed in this invention and the pressure bearing capacity of 2mm cracks; Figure 6 This is a line graph showing the change in the strength retention rate of the cured body at 120℃ during thermal aging, as proposed in this invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] Core Implementation Example 1: A plugging system adapted for shallow low-temperature formations at 50~60℃ This embodiment addresses the shortcomings of existing systems, such as slow low-temperature curing and premature gelation.

[0025] Preparation of paraffin thermosensitive microcapsules: The raw materials are selected by mass parts as follows: core material 100 parts of industrial grade 3-diethylaminopropylamine, wall material 78 parts of 48# fully refined paraffin, amphiphilic modifier PEG-400 10 parts, low temperature compatibilizer lauryl alcohol 3 parts, and dispersion medium 60℃ deionized water 200 parts.

[0026] Preparation steps: A1 The reactor was kept at a constant temperature of 60℃, and paraffin, PEG-400 and lauryl alcohol were added. The mixture was stirred at 350r / min for 30min to obtain a uniform molten wax phase. A2: Maintain the reactor temperature at 60℃ and add liquid 3-diethylaminopropylamine. Perform high-speed shearing at 3000r / min for 12min to disperse the amine solution into 5~18μm droplets, forming an oil-in-amine primary dispersion. A3 mixed oil phase was dripped into 15℃ cold water at 8mL / min and stirred at a low speed of 250r / min. Paraffin rapidly solidified and wrapped the amine droplets to form a core-shell structure. A4 Low-temperature drying: Dry in a 40℃ environment with forced air for 4 hours, keeping the temperature below 45℃ throughout the process to avoid softening and damage of the wax shell; A5 sieve analysis yielded intact microcapsule particles of 10-40 mesh. Testing showed that the DSC phase transition trigger temperature of the microcapsules in this embodiment was 48.2-49.3℃, the mass fraction of 3-diethylaminopropylamine was 52.3%, the encapsulation rate was 93.2%, and no amine leakage was observed after standing at 40℃ for 72 hours.

[0027] Preparation of nanocomposite epoxy resin: 50% industrial grade E-51 bisphenol A epoxy resin, 8% OP-10 emulsifier, 20% deionized water, 3.5% polyethylene glycol PEG-3000, 0.5% xanthan gum XC, 1% amino-modified nano silica with a particle size of 20nm, and 1% 100-mesh alkali-hydrolyzed lignin powder were selected by mass percentage. The base liquid does not contain any free amine curing agents.

[0028] Preparation steps: B1 Preheat epoxy resin in a 45°C water bath, add OP-10 and stir to mix, add deionized water dropwise at a constant pressure funnel for 10 min and continue stirring for 10 min to form a preliminary oil-in-water emulsion. B2 pre-dissolves PEG-3000 in 45°C warm water, pours it all into the emulsion and stirs for 15 minutes, relying on steric hindrance to prevent resin droplet aggregation. Add alkali-hydrolyzed lignin powder to B3 under low-speed stirring and stir for 8 minutes. Then slowly add amino-modified nano-silica that has been ultrasonically dispersed for 10 minutes to eliminate agglomeration to the emulsion and stir for 12 minutes. B4 was slowly added to xanthan gum XC dry powder and stirred continuously for 15 minutes to obtain a milky white stable nanocomposite epoxy liquid. After a 14-day accelerated aging test at 54℃ (simulating 6 months of storage at room temperature), no stratification, sedimentation or performance degradation was observed in the system.

[0029] On-site pulp preparation and application: The pre-prepared base liquid of C1 is stored in a sealed container at room temperature; Before C2 sealing operation, add paraffin thermosensitive microcapsules. After calculation, the mass of 3-diethylaminopropylamine contained in the microcapsules accounts for 9% of the total mass of the system. Stir at 300 r / min for 5 min until the particles are uniformly suspended to obtain the sealing working solution. All amine curing agents exist in the form of microcapsule core material, with no free amine. C3 pumps the working fluid directly into the wellbore.

[0030] Testing showed that the viscosity change rate of the working solution in this embodiment after standing at 25°C for 48 hours was 7.2%, with no premature gelation. The pumping window was 65 minutes, the complete curing time at 60°C was 120 minutes, the compressive strength of the cured body was 58 MPa, the strength retention rate after aging at 120°C for 6 days was 71%, and the pure system with a 2mm crack withstand pressure of 6.5 MPa. This addresses the shortcomings of insufficient curing rate and premature gelation at low temperatures.

[0031] Example 2: Low Resin Content Adaptation System In this embodiment, the composition of the microcapsule was as follows: 40% bisphenol A epoxy resin, 12% OP-10 emulsifier, 25% deionized water, 5% PEG-3000, 1.0% xanthan gum XC, 2.0% amino-modified nano silica, and 2.0% alkali-hydrolyzed lignin powder. For microcapsule preparation, the wall material consisted of 70 parts paraffin wax, 8 parts PEG-400, 2 parts lauryl alcohol, and the dispersion medium was 180 parts deionized water. The microcapsule preparation steps were the same as in Example 1. The microcapsule encapsulation rate was 92.1%, which translates to 7% of the total mass of 3-diethylaminopropylamine in the system.

[0032] The preparation, on-site mixing, and application steps of the nanocomposite epoxy-based liquid were completely consistent with those in Example 1. Testing showed that the viscosity change rate of the working liquid after standing at 25°C for 48 hours was 8.1%, the pumping window was 58 minutes, the complete curing time at 55°C was 135 minutes, the compressive strength of the cured body was 47 MPa, the strength retention rate after aging at 120°C for 6 days was 69%, and the compressive strength of a 2mm crack was 5.8 MPa.

[0033] Example 3 High Resin Proportion Adaptation System In this embodiment, the composition of the microcapsule was as follows: 60% bisphenol A type epoxy resin, 5% OP-10 emulsifier, 15% deionized water, 2% PEG-3000, 0.2% xanthan gum XC, 0.5% amino-modified nano silica, and 0.5% alkali-hydrolyzed lignin powder. For microcapsule preparation, the wall material consisted of 85 parts paraffin wax, 12 parts PEG-400, 4 parts lauryl alcohol, and the dispersion medium was 220 parts deionized water. The microcapsule preparation steps were the same as in Example 1. The resulting microcapsule encapsulation rate was 92.7%, which translates to 11% of the total mass of 3-diethylaminopropylamine in the system.

[0034] The preparation, on-site mixing, and application steps of the nanocomposite epoxy-based liquid were completely consistent with those in Example 1. Testing showed that the viscosity change rate of the working liquid after standing at 25°C for 48 hours was 6.3%, the pumping window was 32 minutes, the complete curing time at 70°C was 95 minutes, the compressive strength of the cured body was 62 MPa, the strength retention rate after aging at 120°C for 6 days was 73%, and the compressive strength of a 2mm crack was 6.8 MPa.

[0035] Example 4: Leakage sealing system adapted to 80℃ high-temperature formations This embodiment adds 0.4% of the total mass of 2,3-dihydroxynaphthalene retarding agent to the base liquid based on Example 1. The retarding agent is added directly to the base liquid in powder form after the xanthan gum is dissolved in step B4 and before the microcapsules are added. The mixture is stirred at 400 r / min for 15 min until completely dissolved. The 3-diethylaminopropylamine equivalent of the microcapsules accounts for 10% of the total mass of the system. The remaining steps of the preparation, on-site mixing and application of the nanocomposite epoxy liquid are completely consistent with those of Example 1.

[0036] Testing showed that the working fluid had a viscosity change rate of 7.8% after standing at 25℃ for 48 hours, a pumping window of 28 minutes, and a complete curing time of 90 minutes at 80℃, with no premature polymerization. The cured body had a compressive strength of 59 MPa, a strength retention rate of 70% after aging at 120℃ for 6 days, and a compressive strength of 6.6 MPa for a 2mm crack. This effectively addresses the defect of rapid curing at high temperatures that easily leads to pipe blockage.

[0037] Example 5: Wide-Crack Compound Application System This embodiment addresses leakage conditions caused by wide cracks with an aperture of 1 mm or more. The sealing working fluid prepared in Example 1 is compounded with a bridging sealing slurry at a volume ratio of 4:1. The bridging sealing slurry, by mass percentage, consists of 2% 7-10 mesh walnut shells, 5% 10-20 mesh quartz sand, 3% 20-40 mesh limestone, 0.3% plant fiber, 0.2% xanthan gum XC, and the balance being water. The preparation and application steps are completely consistent with Example 1. Testing showed that the compound system had a pumping window of 52 minutes, a pressure resistance of 8.7 MPa for a 2 mm crack, and a filtration loss of 6.2 mL in 1 hour with the sand bed, thus addressing the deficiency of insufficient pressure resistance in sealing wide cracks.

[0038] Comparative Example Comparative Example 1: Existing ordinary water-based epoxy sealant system This comparative example uses a commercially available conventional water-based epoxy sealant system, composed of 50% bisphenol A epoxy resin, 8% OP-10 emulsifier, 22% deionized water, 3.5% PEG-3000, and 0.5% xanthan gum XC, with 9% free 3-diethylaminopropylamine added directly. No microcapsules, amino-modified nano-silica, or alkali-hydrolyzed lignin are added. After preparation, gelation begins within 12 minutes at 25°C, with a pumping window of only 10 minutes. The cured body exhibits a compressive strength of 32 MPa, a strength retention rate of 31% after 6 days of aging at 120°C, and a compressive strength of 3.4 MPa for a 2mm crack. This addresses the shortcomings of existing technologies, such as easy pipe clogging, poor mechanical properties, and insufficient temperature resistance.

[0039] Comparative Example 2: Conventional Bridging and Leak-Sealing System This comparative example uses a commonly used field bridging and sealing grout, composed of 2% 7-10 mesh walnut shells, 5% 10-20 mesh quartz sand, 3% 20-40 mesh limestone, 0.3% plant fiber, and the remainder water by weight. The grout has a bearing capacity of 2.1 MPa for a 2mm opening crack. After rinsing with water for 2 hours, the sealing layer completely failed and re-leaked, addressing the shortcomings of existing granular bridging grouts, which lack chemical bonding and are prone to instability and re-leaking.

[0040] Performance Testing Methodology Description The performance data in the following embodiments and comparative examples were all measured using a uniform method: DSC phase transition trigger temperature: determined by differential scanning calorimetry, with a heating rate of 5℃ / min, under nitrogen atmosphere, and the endothermic peak initiation temperature is recorded as the phase transition trigger temperature.

[0041] Microcapsule encapsulation rate: determined by Soxhlet extraction with acetone as solvent, extraction temperature 80℃, extraction time 72h, encapsulation rate = (actual core material mass / theoretical core material mass) × 100%.

[0042] Amine leakage rate: The microcapsules were placed in a specified temperature environment and left to stand for 72 hours. The free amine content was determined by non-aqueous titration. Leakage rate = (mass of free amine / total mass of microcapsule core material) × 100%.

[0043] Release completion time at 50℃: The microcapsules were placed in a constant temperature water bath at 50℃, and the amount of amine released into the aqueous phase was monitored by acid-base titration. The time required for the release rate to reach 100% was recorded as the release completion time.

[0044] Viscosity change rate: Measured using a six-speed rotational viscometer, shear rate 170 s. -1 The test temperature was 25℃, and the rate of change was calculated as (viscosity at time t - initial viscosity) / initial viscosity × 100%.

[0045] Pumping window: The pumping window ends when the system viscosity reaches three times the initial viscosity, and is continuously monitored using a rotational viscometer.

[0046] Complete curing time: The complete curing time was recorded as the time when the exothermic peak of the curing reaction ended, using differential scanning calorimetry (DSC) isothermal scanning.

[0047] Compressive strength: Refer to GB / T 2567-2021 "Test Methods for Performance of Resin Castings", specimen size 20mm×20mm×20mm, loading rate 2mm / min.

[0048] Strength retention rate after aging at 120℃ for 6 days: After curing, the specimens were placed in a constant temperature oven at 120℃ for 6 days. After cooling to room temperature, the compressive strength was tested. Retention rate = (strength after aging / initial strength) × 100%.

[0049] Crack pressure test: A standard crack simulation device of 2mm×1mm was used, and the pressure was increased stepwise (initial pressure 1MPa, pressure increased by 0.5MPa every 5min). The pressure at which penetrating leakage occurs was recorded as the breakthrough pressure.

[0050] Filtration loss of sand bed: The sand bed was filled with 20-mesh quartz sand with a thickness of 5cm, and a pressure of 0.7MPa was applied. The volume of the filtrate was measured after 30 minutes.

[0051] Performance test data table and description Table 1 Comparison of Microcapsule Performance Parameters Note: Commercially available microcapsules of the same type are commercially available temperature-controlled epoxy curing agent microcapsules, with a labeled phase change temperature of 50℃.

[0052] Table 1 explains that the microcapsules prepared in each embodiment of the present invention have a coverage rate of over 92%, an amine leakage rate of less than 0.3% at room temperature, and can completely release the curing agent within 10 minutes at 50°C. Compared with commercially available microcapsules, the coverage rate is increased by more than 8%, the leakage rate is reduced by more than 90%, and the phase change trigger temperature is stable in the range of 48~50°C, meeting the requirements of temperature-sensitive controlled release and effectively solving the defect of existing microcapsules that are prone to leakage and cause premature gelation of the system.

[0053] Table 2 Comparison of Overall Performance of Leak-Plugging Systems Note: Comparative Example 2 is a pure particulate bridging system with no chemical curing reaction. It does not involve viscosity change rate, pumping window, cured compressive strength and aging retention rate indicators, and is represented by " / ".

[0054] Table 2 explains that the viscosity change rate of the system in each embodiment of the present invention at room temperature is less than 10%, there is no premature gelation, and the pumping window coverage of 28~65min can meet the requirements of different construction distances. The curing strength, aging resistance and pressure resistance are all better than the ordinary epoxy system of Comparative Example 1 and the bridging system of Comparative Example 2. The pressure resistance after compounding the bridging grout can reach up to 8.7MPa, which is 156% higher than that of the ordinary epoxy system. It effectively solves the defects of low pressure resistance, easy leakage and poor temperature resistance of the existing system.

[0055] refer to Figure 3 This figure visually illustrates the core performance differences between the microcapsules of this invention and similar commercially available products. Existing commercially available temperature-controlled epoxy curing agent microcapsules are limited by their encapsulation process, generally suffering from low encapsulation rates and high core material leakage rates at room temperature. This easily leads to premature cross-linking and gelation of the plugging system during surface preparation and wellbore pumping, causing pipe blockage accidents. The microcapsule encapsulation rates of all embodiments of this invention are consistently above 92%, an improvement of more than 8% compared to commercially available products. The amine leakage rate after 72 hours of static storage at room temperature is less than 0.3%, a reduction of more than 90% compared to commercially available products. This fully verifies the stability of the microcapsule core-shell structure and the reliability of temperature-sensitive controlled release, preventing system failure caused by premature curing agent leakage from the source and solving the core defect of uncontrollable curing time in existing plugging systems.

[0056] refer to Figure 4This figure visually illustrates the differences in construction adaptability and sealing performance between the system of this invention and existing conventional leak-sealing systems. Existing leak-sealing systems generally suffer from the inability to simultaneously achieve a suitable pumping window and curing rate. Ordinary epoxy systems have a pumping window of less than 15 minutes, easily leading to pipe blockage; bridging particle systems lack chemical bonding, and their sealing pressure resistance is less than 2.5 MPa, easily resulting in re-leakage. The systems of this invention cover a pumping window of 28-65 minutes in each embodiment, adapting to different construction scenarios such as shallow long-distance pumping and high-temperature short-distance pumping. The pure system maintains a stable crack pressure resistance of 5.8-6.8 MPa, while the pressure resistance after adding bridging grout can reach 8.7 MPa, an improvement of 156% compared to ordinary epoxy systems and 314% compared to conventional bridging systems. It simultaneously meets the requirements of long pumping cycles and high sealing pressure resistance, solving the core defects of existing systems such as easy pipe blockage and easy re-leakage.

[0057] refer to Figure 5 This figure visually illustrates the difference in temperature aging resistance between the system of this invention and existing epoxy systems. Existing conventional water-based epoxy plugging systems suffer from low cross-linking network density and poor temperature resistance, making them prone to chain segment degradation in high-temperature downhole environments. This leads to rapid attenuation of the plugging layer strength, short service life, and frequent re-leakage. The system of this invention, by adding amino-modified nano-silica and alkali-hydrolyzed lignin to fill the defects in the cross-linking network, maintains a strength retention rate of 69%–73% after 6 days of heat aging, an improvement of over 120% compared to the conventional epoxy system in Comparative Example 1. Even after 8 days of aging, it retains over 60% of its initial strength, significantly improving long-term temperature aging resistance. This solves the core defects of existing systems, such as narrow temperature range adaptability and poor long-term service stability, making it suitable for various formation plugging needs from 50 to 80°C.

[0058] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A temperature-sensitive, nano-toughened, waterborne epoxy synergistic consolidation and plugging system for plugging leaks in oil and gas drilling fractured, broken, or highly permeable formations, characterized in that... The system is composed of the following components by weight percentage: 40%–60% bisphenol A type epoxy resin, 5%–12% OP-10 emulsifier, 15%–25% deionized water, 2%–5% polyethylene glycol PEG-3000, 0.2%–1.0% xanthan gum XC, 0.5%–2.0% amino-modified nano-silica, 0.5%–2.0% alkali-hydrolyzed lignin powder, and paraffin thermosensitive microcapsules; the paraffin thermosensitive microcapsules are core-shell structured microcapsules made of 48# fully refined paraffin wax as the shell material and 3-diethylaminopropylamine as the core material, with a phase transition trigger temperature of 48℃–50℃; the system does not contain free amine curing agents, and all 3-diethylaminopropylamine exists in the form of the core material of the paraffin thermosensitive microcapsules; the amount of paraffin thermosensitive microcapsules added is based on the mass of 3-diethylaminopropylamine contained in them accounting for 7%–11% of the total mass of the system.

2. The waterborne epoxy synergistic consolidation and plugging system with temperature-sensitive nano-toughened coating according to claim 1, characterized in that, The raw materials for preparing the paraffin thermosensitive microcapsules, by weight, include: 100 parts of core material 3-diethylaminopropylamine, 70-85 parts of wall material 48# fully refined paraffin, 8-12 parts of amphiphilic modifier PEG-400, 2-4 parts of low-temperature compatibilizer lauryl alcohol, and 180-220 parts of dispersion medium 60℃ deionized water; the mass fraction of 3-diethylaminopropylamine in the paraffin thermosensitive microcapsules is 49%-56%.

3. The waterborne epoxy synergistic consolidation and plugging system with temperature-sensitive nano-toughened coating according to claim 2, characterized in that, The paraffin thermosensitive microcapsules have a particle size of 10-40 mesh, a core material coverage rate of not less than 92%, and no amine substances leak when the ambient temperature is below 45℃; the leak-sealing system, when left to stand for 48 hours at an environment of 20℃-40℃, has a viscosity change rate of no more than 10% and no premature gelation phenomenon.

4. The waterborne epoxy synergistic consolidation and plugging system with temperature-sensitive nano-toughened coating according to claim 1, characterized in that, The system is suitable for lost formations with temperatures ranging from 50°C to 80°C. In the system suitable for shallow low-temperature formations with temperatures ranging from 50°C to 60°C, the mass of 3-diethylaminopropylamine in the paraffin thermosensitive microcapsules accounts for 8.5% to 10.5% of the total mass of the system. In the system suitable for high-temperature formations with temperatures ranging from 70°C to 80°C, 0.3% to 0.5% of 2,3-dihydroxynaphthalene retarder is also added to the system.

5. A method for preparing the thermosensitive nano-toughened waterborne epoxy synergistic consolidation and plugging system according to any one of claims 1 to 4, characterized in that, Paraffin thermosensitive microcapsules and nanocomposite epoxy liquid were prepared independently. The nanocomposite epoxy liquid did not contain free amine curing agents. Before on-site leak sealing construction, the paraffin thermosensitive microcapsules were mixed into the nanocomposite epoxy liquid and stirred at a speed of 200 r / min to 400 r / min for 3 min to 8 min until the particles were uniformly suspended.

6. The preparation method according to claim 5, characterized in that, The preparation of the paraffin thermosensitive microcapsules includes the following steps: A1. Low-temperature melt modified paraffin: The reaction vessel is kept at a constant temperature of 60℃, and 48# fully refined paraffin, PEG-400 and lauryl alcohol are added. The mixture is stirred at 350r / min for 30min to obtain a uniform melted wax phase. A2. Core material dispersion and emulsification: Maintain the reactor temperature at 60℃, add liquid 3-diethylaminopropylamine, and shear at 3000r / min for 12min to disperse the amine liquid into tiny droplets of 5μm~18μm, forming an oil-coated amine primary dispersion. A3. Low-temperature quenching and forming: The mixed oil phase is dripped into cold water at 15℃ at a rate of 8mL / min and stirred at a speed of 250r / min. The low-temperature paraffin rapidly solidifies and encapsulates the amine droplets to form a complete core-shell structure. A4. Low-temperature drying: Dry in a 40℃ environment with forced air for 4 hours, and keep the temperature below 45℃ throughout the process; A5. Screening and grading: Screening to obtain complete microcapsule particles of 10-40 mesh for later use.

7. The preparation method according to claim 5, characterized in that, The preparation of the nanocomposite epoxy liquid includes the following steps: B1. Resin emulsification: Take a measured amount of bisphenol A epoxy resin and preheat it in a 45°C water bath. Add OP-10 emulsifier and stir to mix. Add deionized water dropwise at a uniform rate over 10 minutes through a constant pressure funnel and continue stirring for 10 minutes to form a preliminary oil-in-water emulsion. B2. Introduction of dispersion stabilization system: The metered polyethylene glycol PEG-3000 is pre-dissolved in warm water, poured into the emulsion and stirred for 15 min. The steric hindrance of PEG prevents the resin droplets from agglomerating and separating. B3. Stepwise doping of bifunctional fillers: First, add alkaline hydrolyzed lignin powder under stirring conditions of 250 r / min and stir for 8 min. Then, slowly add the emulsion after ultrasonic dispersion for 10 min and stir for 12 min. B4. Thickening and suspension control: Slowly add xanthan gum XC dry powder and stir continuously for 15 minutes to obtain a stable milky white nano-composite epoxy liquid.

8. The application of the temperature-sensitive nano-toughened waterborne epoxy synergistic consolidation and plugging system according to any one of claims 1 to 4, characterized in that, Used for plugging leaks in oil and gas drilling formations at temperatures ranging from 50℃ to 80℃.

9. The application according to claim 8, characterized in that, For wide cracks or karst caves with an opening of more than 1 mm, the aforementioned sealing system and bridging sealing slurry are mixed and used at a volume ratio of 4:

1. The bridging sealing slurry is composed of 2% 7-10 mesh walnut shells, 5% 10-20 mesh quartz sand, 3% 20-40 mesh limestone, 0.3% plant fiber, 0.2% xanthan gum XC, and the balance being water by mass percentage.

10. The application according to claim 8 or 9, characterized in that, On-site construction includes the following steps: C1. Prepare a nanocomposite epoxy liquid without paraffin-free thermosensitive microcapsules and store it in a sealed container at room temperature; C2. Before the leak sealing operation, add a measured amount of paraffin thermosensitive microcapsules to the nanocomposite epoxy liquid, and stir at a speed of 200r / min to 400r / min for 3min to 8min until the particles are uniformly suspended to prepare the leak sealing working solution. C3. The plugging fluid is directly pumped into the wellbore. After the working fluid enters the lost formation, the paraffin thermosensitive microcapsules melt and release the curing agent, triggering the epoxy cross-linking reaction to form a solidified sealing layer.

Citation Information

Patent Citations

  • Self-cementing plugging agent and plugging method

    CN107674662A

  • Epoxy-based LCM compositions with controlled viscosity and methods of treating a lost circulation zone of a wellbore

    US11370956B2

  • Method for Drilling and Completion Operations with Settable Resin Compositions

    US20130008654A1